Capillary and microchip electrophoresis method development for amino acid monitoring during biopharmaceutical cultivation. Issue 8 (13th May 2022) - Mikkonen, Saara; Josefsson, Leila; Mäkinen, Meeri E.‐L.; Chotteau, Veronique; Emmer, Åsa
Abstract: The increased use of biopharmaceuticals calls for improved means of bioprocess monitoring. In this work, capillary electrophoresis (CE) and microchip electrophoresis (MCE) methods were developed and applied for the analysis of amino acids (AAs) in cell culture supernatant. In samples from different days of a Chinese hamster ovary cell cultivation process, all 19 proteinogenic AAs containing primary amine groups could be detected using CE, and 17 out of 19 AAs using MCE. The relative concentration changes in different samples agreed well with those measured by high‐performance liquid chromatography (HPLC). Compared to the more commonly employed HPLC analysis, the CE and MCE methods resulted in faster analysis, while significantly lowering both the sample and reagent consumption, and the cost per analysis. Graphical Abstract and Lay Summary: In this article, capillary electrophoresis (CE) and microchip electrophoresis (MCE) methods for monitoring amino acids (AAs) in mammalian cell culture samples are presented. The developed CE and MCE methods are faster, more cost‐effective, and consume fewer samples and chemicals compared to the currently used high‐performance liquid chromatography‐based approach. The MCE methods further represent a proof‐of‐concept toward developing an automated platform for at‐line bioprocess monitoring of AAs.